Security and Development : Searching for Critical Connections - Edited By Tschirgi, Necla; Lund Michael S; Mancini, Francesco (New Dehli Viva Books, 2011)
Although policymakers and practitioners alike have enthusiastically embraced the idea that security and development are interdependent, the precise nature and implications of the dynamic interplay between the two phenomena have been far from clear. The authors of Security and Development: Searching for Critical Connections realistically assess the promise and shortcomings of integrated security-development policies as a strategy for conflict prevention. Addressing cross-cutting issues and also presenting detailed country case studies, they move beyond rhetoric and generalization to make an important contribution to the international conflict prevention agenda.
Include Index and Bibliography.
Keywords: Political violence -- Civil war--Economic aspects